Evaluating gaze behaviors as pre-touch reactions for virtual agents - Cuello Mejía, Dario Alfonso; Sumioka, Hidenobu; Ishiguro, Hiroshi; Shiomi, Masahiro (Frontiers in Psychology, 2023)
Reaction behaviors by human-looking agents to nonverbal communication cues significantly affect how they are perceived as well as how they directly affect interactions. Some studies have evaluated such reactions toward several interactions, although few approached before-touch situations and how the agent’s reaction is perceived. Specifically, it has not been considered how pre-touch reactions impact the interaction, the influence of gaze behavior in a before-touch situation context and how it can condition the participant’s perception and preferences in the interaction. The present study investigated the factors that define pre-touch reactions in a humanoid avatar in a virtual reality environment and how they influence people’s perceptions of the avatars. We performed two experiments to assess the differences between approaches from inside and outside the field of view (FoV) and implemented four different gaze behaviors: face-looking, hand-looking, face-then-hand looking and hand-then-face looking behaviors. We also evaluated the participants’ preferences based on the perceived human-likeness, naturalness, and likeability. In Experiment 1, we evaluated the number of steps in gaze behavior, the order of the gaze-steps and the gender; Experiment 2 evaluated the number and order of the gaze-steps. Our results showed that two-step gaze behavior was perceived as more human and more natural from both inside and outside the field of view and that a face-first looking behavior when defining only a one-step gaze movement was preferable to hand-first looking behavior from inside the field of view. Regarding the location from where the approach was performed, our results show that a relatively complex gaze movement, including a face-looking behavior, is fundamental for improving the perceptions of agents in before-touch situations. This can be very useful for increasing the immersion and enhance the experience in Virtual Reality environments, extending the frontiers of haptic interaction and complementing the already studied nonverbal communication cues.